A Scalable Synthesis of Chiral Himbert Diene Ligands for Asymmetric Catalysis - LI, Hongyi (2024)
Here, is presented a intramolecular [4+2] cycloaddition of a simply attained chiral allenecarboxanilide readily affords pseudoenantiomeric bicyclo[2.2.2]octa-2,5-dienes containing an alkenyl bromide, which can be readily functionalized to give diverse chiral diene ligands. The synthesis is straightforward and easily conducted on multigram scales. These ligands exhibit high performance in nine types of enantioselective Rh(I)-catalyzed 1,4-addition or 1,2-addition reactions, with up to 99% yield and >99% ee.